2018
DOI: 10.1186/s12944-018-0915-1
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and characterization of long non-coding RNAs during postnatal development of rabbit adipose tissue

Abstract: BackgroundThe rabbit is widely used as an important experimental model for biomedical research, and shows low adipose tissue deposition during growth. Long non-coding RNAs (lncRNAs) are associated with adipose growth, but little is known about the function of lncRNAs in the rabbit adipose tissue.MethodsDeep RNA-sequencing and comprehensive bioinformatics analyses were used to characterize the lncRNAs of rabbit visceral adipose tissue (VAT) at 35, 85 and 120 days after birth. Differentially expressed (DE) lncRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 75 publications
4
14
0
Order By: Relevance
“…The vast majority of putative lncRNAs were intronic or intergenic in our study, which confirmed that intragenic and intergenic regions were the major sources of non-coding RNAs (Mattick and Makunin 2006;Xu, Bai, et al 2017). lncRNAs are known to be shorter transcript lengths and fewer exon numbers than mRNAs (Wang et al 2018;Sulayman et al 2019). Approximately 80.51% of our 4155 lncRNAs was shorter than 2800 bp and 87.32% of them had 2-4 exons, which was in agreement with previous studies in cattle (Billerey et al 2014;Liu et al 2017;Choi et al 2019;Yue et al 2019).…”
Section: Discussionsupporting
confidence: 92%
“…The vast majority of putative lncRNAs were intronic or intergenic in our study, which confirmed that intragenic and intergenic regions were the major sources of non-coding RNAs (Mattick and Makunin 2006;Xu, Bai, et al 2017). lncRNAs are known to be shorter transcript lengths and fewer exon numbers than mRNAs (Wang et al 2018;Sulayman et al 2019). Approximately 80.51% of our 4155 lncRNAs was shorter than 2800 bp and 87.32% of them had 2-4 exons, which was in agreement with previous studies in cattle (Billerey et al 2014;Liu et al 2017;Choi et al 2019;Yue et al 2019).…”
Section: Discussionsupporting
confidence: 92%
“…This biological mechanism is also related to insulin response (Richardson & Herd, 2004), which supports the relationship between insulin genes and FE, as previously stated. Indeed, several lipid‐related genes were identified, such as SDCBP (Santos, 2018), ACLY (Ji, Osorio, Drackley, & Loor, 2012), OLR1 (Vinsky, Islam, Chen, & Li, 2013), CRTC3 (Raza et al., 2019), PRKDC (Horodyska, Hamill, Varley, Reyer, & Wimmers, 2017), HNRNPA3 (Wang et al., 2018), HTATIP2 (Liao et al., 2014) and NFE2L2 (Wu, Cui, & Klaasen, 2011) genes. The OLR1 and CRTC3 genes were reported associated with body weight, rib eye area and fat thickness in Nellore (Fonseca et al., 2015), and fat deposition in Qinchuan cattle (Raza et al., 2019), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to lncRNAs(Wang et al 2018a), miRNAs and the target genes of DE miRNAs were mainly involved in GO functional terms including metabolic process, cell process and single organism process in the classification of biological processes, partial cells and organisms in the classification of cell components, and binding and catalytic activity in the classification of molecular functions. Based on our in-depth analysis of the 1048 significantly enriched GO terms, it was found that amongst the top 10 GO terms of biological process, cell composition and molecular function, some terms that strongly promote growth and volume increases in adipocytes, including protein localization to the plasma membrane, protein ubiquitination involved in ubiquitin-dependent protein catabolic process, regulation of cell growth, cytoplasm, Golgi apparatus, membrane, protein binding, protein tyrosine phosphatase, zinc ion binding, ATP binding, and cadherin binding were identified.…”
Section: Discussionmentioning
confidence: 99%